JP 1 : Art International = Internationale Kunst. - Baudson, Michel; Delevoy, Robert-L.; Dypréau, Jean; Geirlandt, Karel J.; Langui, Emile; Legrand, Francine-Claire; Mertens, Phil; Van Tieghem, Jean-Pierre; Exhibition. JP 1 : Art International = Internationale Kunst. Brussel. Bozar - Paleis voor Schone Kunsten Brussel. 1975-07-18. 1975-08-31 (Brussel : Bozar - Paleis voor Schone Kunsten Brussel Jeune Peinture Belge vzw Brussel, 1975)
van Amen, Woody ; Anthoons, Willy ; Arroyo, Eduardo ; Barbaix, René ; Bauermeister, Mary ; Bertrand, Gaston ; Bonnet, Anne ; Collignon, George ; Cox, Jan ; Delahaut, Jo ; Dotremont, Christian ; Elias, Etienne ; Fahlström, Öyvind ; Girke, Raimund ; Godderis, Jack ; Haacke, Hans ; Hofkunst, Alfred ; Lacomblez, Jacques ; Lennep, Jacques ; Van Lint, Louis ; Lismonde ; Mahy, Emile ; Mendelson, Marc ; Mestdagh, Roberte ; Milo, Jean ; Mortier, Antoine ; Nellens, Roger ; Opalka, Roman ; Panamarenko ; Peire, Luc ; Pry, Charles ; Quinet, Mig ; Roobjee, Pjeroo ; Simonetti, Gianni Emilio ; Slabbinck, Rik ; Wéry, Marthe
biog. per kunstenaar
Frans
Nederlands
boek